Advances in the Casimir effect - Bordag, Michael, 1952- (Oxford : Oxford University Press, 2009)
This title is a comprehensive sourcebook, distilled from hundreds of recently published papers, about the Casimir effect: the small forces originating from the quantum vacuum and acting between closely spaced bodies. It brings together developments in experiment and theory, fundamental and applied aspects of the Casimir force.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Casimir effect